(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the legal implications of Constitutional Court Decision Number 135/PUU-XXII/2024 concerning the separation between National Elections and Regional Elections, as well as to examine the continuity of the decision if the Regional Head Election system is changed from direct to indirect elections. This research employs a normative juridical method with statutory, conceptual, case, and historical approaches. This study applies the theories of Distribution of Power, Stufenbau Theory, and Shared Responsibility Theory, while also developing the Legal Emotion Concept as an analytical approach. The analysis is conducted qualitatively through the interpretation of primary, secondary, and tertiary legal materials. The findings indicate that Constitutional Court Decision Number 135/PUU-XXII/2024 establishes a new construction in the form of National Elections and Regional Elections. However, its implementation potentially creates constitutional disharmony regarding the term of office of regional legislative councils and the synchronization of elections. This study also finds that the sustainability of the “Regional Election” construction highly depends on the legal political direction of lawmakers in Indonesia. This study is limited to a normative legal approach. Further research is recommended to adopt an empirical or socio-legal approach to examine the implementation of Constitutional Court Decision No. 135/PUU-XXII/2024 and the validity of the Concept of Legal Emotions in constitutional practice.